2006
DOI: 10.1109/tip.2006.881939
|View full text |Cite
|
Sign up to set email alerts
|

Recovering DC Coefficients in Block-Based DCT

Abstract: It is a common approach for JPEG and MPEG encryption systems to provide higher protection for dc coefficients and less protection for ac coefficients. Some authors have employed a cryptographic encryption algorithm for the dc coefficients and left the ac coefficients to techniques based on random permutation lists which are known to be weak against known-plaintext and chosen-ciphertext attacks. In this paper we show that in block-based DCT, it is possible to recover dc coefficients from ac coefficients with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 8 publications
0
54
0
Order By: Relevance
“…Unfortunately, if too many syntax elements containing perceptual information are left unencrypted, the security might be compromised. A lot of research [1,8,23,24,26,31,37,39,41] has shown that some perceptual information can be recovered from various kinds of unencrypted syntax elements. This problem is due to the following fact: most multimedia coding standards are designed in such a way that many syntax elements can be decoded independently without decoding other syntax elements.…”
Section: Multimedia Encryptionmentioning
confidence: 99%
“…Unfortunately, if too many syntax elements containing perceptual information are left unencrypted, the security might be compromised. A lot of research [1,8,23,24,26,31,37,39,41] has shown that some perceptual information can be recovered from various kinds of unencrypted syntax elements. This problem is due to the following fact: most multimedia coding standards are designed in such a way that many syntax elements can be decoded independently without decoding other syntax elements.…”
Section: Multimedia Encryptionmentioning
confidence: 99%
“…that missing DC coefficients cannot be effectively recovered, before Uehara et al reported in [22] that one can approximately recover missing DC coefficients by exploiting the fact that the difference of neighboring pixel values in natural images observes a Laplace distribution with zero mean and small variance [18]. Their method generally works well and is computationally efficient, but the perceptual quality of the recovered image is not always good enough.…”
Section: Related Workmentioning
confidence: 99%
“…We observed that around 94.04% of the ACs lie in the range of 0 to 20. This is due to the fact that lower frequency AC coefficients carry less energy [14]. Figure 3 shows the percentage occupied by the quadruples, whose AC coefficient ranges is in 0-20 (orange) and 20-255 (dark-blue).…”
Section: Basis For Our Algorithmmentioning
confidence: 99%
“…The encryption of the DC value plays a key role in the visibility of the video block. Some encryption algorithms only encrypt the DC coefficient while simply permutating the ACs [14]. In order to enhance the security, we apply CBC mode for encrypting the DC coefficients rather than the general ECB mode which is applied for the AC coefficients.…”
Section: Algorithm 1 Pre-processingmentioning
confidence: 99%